Pengaruh Kreativitas, Inovasi dan Ekspektasi Pendapatan terhadap Minat Berwirausaha Mahasiswa : (Studi Kasus Akademi Kesejahteraan Sosial Ibu Kartini) - Agus Susanti (Garina, 2025)
This study aims to determine the effect of creativity, innovation, and income expectations on the entrepreneurial interest of students at the Ibu Kartini Social Welfare Academy (AKS). The approach used is quantitative, with data collection techniques through questionnaires distributed to all students in semesters IV, VI, and VIII who have taken entrepreneurship courses, with a total number of respondents of 94 people (using census techniques). The data were analyzed using multiple linear regression analysis with the help of SPSS version 20. The results showed that the three independent variables (creativity, innovation, and income expectations) simultaneously had a significant effect on students' interest in entrepreneurship. However, partially, the income expectation variable had the most dominant effect on interest in entrepreneurship. The conclusion of this study shows that the expectation of higher income is the main motivation for students to enter the world of entrepreneurship. Therefore, strategies to increase entrepreneurial interest need to be focused on increasing students' understanding of the potential income in entrepreneurial activities as well as providing real facilities and support from the campus and external parties.